An additional patient with a homozygous mutation in DCPS contributes to the delination of Al‐Raqad syndrome. Issue 12 (5th October 2018) - Alesi, Viola; Capolino, Rossella; Genovesea, Silvia; Capriati, Teresa; Loddo, Sara; Calvieri, Giusy; Calacci, Chiara; Diociaiuti, Andrea; Diamanti, Antonella; Novelli, Antonio; Dallapiccola, Bruno
Abstract : DCPS gene encodes for a protein involved in gene expression regulation through promoting cap degradation during mRNA decapping processes. Mutations altering the DCPS function have been associated to a distinct disorder, Al‐Raqad syndrome, so far described only in two families. We report on a patient harboring a novel homozygous missense mutation in DCPS, presenting with growth retardation, craniofacial anomalies, skin dyschromia, and neuromuscular defects. This case study explains the molecular spectrum of DCPS mutations and might contribute to the phenotypic delineation of this rare condition.